Short-term feeding of different levels of white grape pomace silage in dairy goats: impacts on milk yield, nutritional efficiency, and metabolic responses - Galvez-Lopez, Marina; Romero, Gema; Sandoval-Castro, Carlos Alfredo; Perez, Elena; Rodriguez, Martín; Peris, Cristòfol; Díaz, Jose Ramón (Frontiers in Animal Science, 2025)
Grape pomace is the winery’s main byproduct, with an estimated 260 million tons generated annually. It includes high concentrations of grape-derived bioactive compounds that may exert beneficial effects on oxidative and biochemical status, and productive performance in the animals, being an environmentally and economically sustainable alternative to conventional raw materials. The effect of incorporating different proportions (0, 5, 10, and 15% DM) of white grape pomace silage (WGP) into isoenergetic and isoproteic diets on the performance of dairy goats was evaluated. Eighty-eight Murciano-Granadina goats were selected and split into 8 homogeneous batches of 11 goats each, according to parity, body weight, milk yield and SCC. After a pre-experimental sampling, every diet was randomly assigned to two batches, and the feeding trial lasted 8 weeks. Biweekly body weight was recorded, and individual milk samples were collected to evaluate both yield and gross composition. The intake of dry and fresh matter and water was recorded weekly at the batch level over two consecutive days. Physiological and oxidative stress, assessed through hemogram, serum biochemical profile, and plasma antioxidant activity (ABTS, FRAP, SOD), were evaluated at the goat level on the pre-experimental and the final experimental samplings. Although a significant decrease in body weight was observed in the 15-WGP treatment, it was not translated into differences in milk yield or composition. Feed efficiency (fat and protein corrected milk/dry matter intake) was higher in WGP diets compared to the control. The 10-WGP and 15-WGP treatments consumed significantly less water than the other treatments. Hematocrit (HCT) increased more markedly in the control than in the WGP-diets treatments. At the last sampling, GLU concentrations in the 15-WGP treatment remained significantly lower than in the other treatments. None of the changes observed in the hemogram or serum biochemical profile were considered physiologically relevant. No dietary effects were detected on the oxidative stress of the animals. In conclusion, the ensiled white grape pomace inclusion in dairy goat diets at levels of up to 15% of dry matter appears to be feasible without inducing short-term adverse effects, provided the diets are nutritionally balanced. However, further research is recommended to confirm long-term safety and performance outcomes.